Migrant Worker Evacuation Strategies in Indonesia’s Overseas Oil and Gas Operations: A Conceptual Approach - Santoso, Imam; Sudirman, M. Iman; Helmi, M. Nurman; Suteja, Jaja; Priadana, M. Sidik; Jamaludin, Maun; Lestari, Fatma (LifeSciFi, 2024)
Migrant worker evacuation strategies are vital for ensuring safety and operational continuity in high-risk sectors, particularly the oil and gas industry. Despite global safety policies, significant challenges in implementing effective evacuation strategies remain, as demonstrated by an Indonesian oil and gas company operating in Algeria and Iraq. Issues such as unclear protocols, limited resources, and poor inter-party coordination persist. This study utilizes a conceptual approach to examine the evacuation management strategies for migrant workers in these high-risk environments through a qualitative multiple case study approach, including interviews, focus group discussions, and AI-driven data analysis. The research identifies strengths in legal frameworks, planning, and technology, but also highlights critical gaps in evaluation, resource allocation, and organizational coordination. These gaps require more integrated and adaptive strategies. The study underscores the importance of communication, digital technology, and robust data protection in improving evacuation efficiency while safeguarding privacy. This research contributes to risk and crisis management literature, offering practical insights for multinational companies in the oil and gas sector. By optimizing migrant worker evacuation strategies, companies can enhance safety, operational sustainability, and crisis resilience, ultimately leading to more comprehensive and effective evacuation plans for their workforce in complex, high-risk environments.